Monitoring Ocean Acidification within State Borders: Lessons from Washington State (USA). Issue 5 (24th June 2021) - Gonski, S. Fisher; Horwith, Micah J.; Albertson, Skip; Bos, Julia; Brownlee, Allison S.; Coleman, Natalie; Maloy, Carol Falkenhayn; Keyzers, Mya; Krembs, Christopher; Pelletier, Greg; Rauschl, Elisa; Young, Holly R.; et al.
Abstract: The Washington State Department of Ecology conducted a large-scale ocean acidification (OA) study in greater Puget Sound to: (1) produce a marine carbon dioxide (CO2 ) system dataset capable of distinguishing between long-term anthropogenic changes and natural variability, (2) characterize how rivers and freshwater drive OA conditions in the region, and (3) understand the relative influence of cumulative anthropogenic forcing on regional OA conditions. Marine CO2 system data were collected monthly at 20 stations between October 2018 and February 2020. While additional data are still needed, the climate-level data collected thus far have uncovered novel insights into spatiotemporal distributions of and variability in the regional marine CO2 system, especially at low salinities in shallow, river-forced shelf regions. The data provide a strong foundation with which to continue monitoring OA conditions across the region. More importantly, this work represents the first successful long-term OA monitoring program undertaken at the state-level by a regulatory agency. Therefore, we offer the work described herein as a blueprint to help state and local scientists and environmental and natural resource managers develop, implement, and conduct long-term OA monitoring programs and studies in their own contexts and jurisdictions.